Screening for Natural Producers Capable of Producing 1,3-Propanediol from Glycerol - Andriani, Dian; Kusharyoto, Wien; Prasetya, Bambang; Wilke, Thomas; Vorlop, Klaus Dieter (Research Center for Biotechnology - Indonesian Institute of Sciences (LIPI), 2010)
Glycerol is a renewable resource found as the mainÂ by-product in the transesterification of triglycerides and fat saponification. Due to the increased production of plant oils, especially palmÂ oilÂ in developing countries, and their larger useÂ by the oleochemical industry, glycerol surpluses are on the world market and this may result in a desrease in glycerolÂ price. As a consequence, biotechnological processesÂ have been developed to convert this substrateÂ intoÂ value-addedÂ products,Â suchÂ asÂ 1,3-propanediolÂ (1,3-PD).Â TheÂ microbialÂ productionÂ ofÂ 1,3-PD couldÂ beÂ competitiveÂ toÂ chemicalÂ routesÂ assumingÂ thatÂ itÂ isÂ basedÂ onÂ cheapÂ rawÂ materialÂ andÂ anÂ optimized process.Â InÂ theÂ screeningÂ forÂ 1,3Â PDâproducingÂ bacteria,Â rawÂ glycerolÂ asÂ by-productÂ fromÂ rapeseedÂ oil processing unitÂ wasÂ usedÂ asÂ aÂ carbonÂ sourceÂ comparedÂ withÂ commercialÂ glycerol.Â ByÂ usingÂ increasing concentration ofÂ bothÂ glycerolsÂ fromÂ 50Â toÂ 150Â g/l,Â twoÂ potentialÂ bacteriaÂ wereÂ obtainedÂ fromÂ soilÂ samples.BMP 1 was obtained from an enrichment culture using 50 g/l commercial glycerol, while BMR-1 was obtained from Â an enrichment culture using 100 g/l raw glycerol. The highest conversion yield obtained using the isolateBMP-1 was around 0.62 g 1,3-PD formed perÂ mol glycerol consumed, and 0.73Â mol 1,3-PDÂ formed perÂ molgycerol using the isolate BMR-1. No bacteria were obtained from cultures using 150 g/l commercial and rawgycerol, respectively, which indicated that higher concentration of glycerol has inhibition effect. Â Keywords: 1,3-propanediol, enrichment culture, glycerol, palm oil, screening